HPV16 E7 oncoprotein test as a triage strategy for HPV16-positive women in cervical cancer screening: long-term follow-up outcome - Wang, Xinmei; Shuai, Guangnan; Xu, Junhui; Liu, Meihua; Zhao, Jianguo; Zhang, Na; Zhang, Wenwen; Qu, Pengpeng (Frontiers in Oncology, 2023)
Backgr ound: Colposcopy is recommended once human papillomavirus (HPV)16/18 infection is detected. However, not all HPV16/18-positive women will necessarily develop cervical lesions. Therefore, this study aimed to investigate the application of quantitative HPV16 E7 oncoprotein detection as a cervical cancer screening method for more efficient screening while minimizing unnecessary colposcopy.Methods: E7 oncoprotein (HPV16) was quantitatively detected in cervical exfoliated cells of HPV16-positive women. The levels of HPV16 E7 oncoprotein in different degrees of cervical lesions were compared, and the optimal cut-off value for identifying HSIL+ was determined by receiver operating characteristic (ROC) curve analysis. With a pathological diagnosis as the gold standard, the sensitivity (SEN), specificity (SPE), positive predictive value (PPV), negative predictive value (NPV), and Kappa value were calculated to verify the diagnostic value of the method. Women diagnosed with low-grade squamous intraepithelial lesions (LSIL) and normal women were followed up for 5 years to evaluate the predictive value of HPV16 E7 protein for disease progression/persistent infection.